KEPEMIMPINAN TRANSFORMASIONAL DI SEKOLAH-SEKOLAH MUHAMMADIYAH - Wahjono, Sentot Imam (Department of Management, 2011)
Universitas Muhammadiyah SurabayaE-mail : totim27@yahoo.comABSTRACTTo avoid the pattern of laissez-faire leadership at the head of Muhammadiyah schools requiredthe application of trans-formational leadership pattern. This is supported by a study evaluating theeffect of Authentic Transformational Leader-ship behaviors of Emotional Intelligence by interveningvariable: Value congruence, Trust and Respect for teachers and employees in Muhammadiyah schools.The sample used in this study were 66 employees and 125 teachers. The results show that thebehavior Authentic Transformational Leadership have a significant influence on EmotionalIntelligence directly. Significant influence is also shown intervening variables: value congruence(posi-tive), Trust (negative) and Respect (negative).Keywords: authentic transformational leadership, emotional intelligence, value congruence, trust,reverence.